Adolescent Initiation of Licit and Illicit Substance Use: Impact of Intrauterine Exposures and Post-natal Exposure to Violence - Frank, Deborah A. (2010)
Whether intrauterine exposures to alcohol, tobacco, marijuana, or cocaine predispose offspring to substance use in adolescence has not been established. We followed a sample of 149 primarily African American/African Caribbean, urban adolescents recruited at term birth until age 16 to investigate intrauterine cocaine exposure (IUCE). We found that in Kaplan-Meier analyses higher levels of IUCE were associated with a greater likelihood of initiation of any substance (licit or illicit), as well as marijuana and alcohol specifically. Adolescent initiation of other illicit drugs and cigarettes were analyzed only in the “any” summary variable since they were used too infrequently to analyze as individual outcomes. In Cox proportional hazard models controlling for intrauterine exposure to alcohol, tobacco, and marijuana and demographic and postnatal covariates, those who experienced heavier IUCE had a greater likelihood of initiation of any substance, and those with lighter intrauterine marijuana exposure had a greater likelihood of initiation of any substance as well as of marijuana specifically. Time-dependent higher levels of exposure to violence between ages of 8 and 16 were also robustly associated with initiation of any licit or illicit substance, and of marijuana, and alcohol particularly.